Picky ABCG5/G8 and promiscuous ABCG2 ‐ a tale of fatty diets and drug toxicity. Issue 23 (14th October 2020) - Khunweeraphong, Narakorn; Mitchell‐White, James; Szöllősi, Dániel; Hussein, Toka; Kuchler, Karl; Kerr, Ian D.; Stockner, Thomas; Lee, Jyh‐Yeuan
Abstract : Structural data on ABCG5/G8 and ABCG2 reveal a unique molecular architecture for subfamily G ATP‐binding cassette (ABCG) transporters and disclose putative substrate‐binding sites. ABCG5/G8 and ABCG2 appear to use several unique structural motifs to execute transport, including the triple helical bundles, the membrane‐embedded polar relay, the re‐entry helices, and a hydrophobic valve. Interestingly, ABCG2 shows extreme substrate promiscuity, whereas ABCG5/G8 transports only sterol molecules. ABCG2 structures suggest a large internal cavity, serving as a binding region for substrates and inhibitors, while mutational and pharmacological analyses support the notion of multiple binding sites. By contrast, ABCG5/G8 shows a collapsed cavity of insufficient size to hold substrates. Indeed, mutational analyses indicate a sterol‐binding site at the hydrophobic interface between the transporter and the lipid bilayer. In this review, we highlight key differences and similarities between ABCG2 and ABCG5/G8 structures. We further discuss the relevance of distinct and shared structural features in the context of their physiological functions. Finally, we elaborate on how ABCG2 and ABCG5/G8 could pave the way for studies on other ABCG transporters.